Profiling the human hair follicle immune system in lichen planopilaris and frontal fibrosing alopecia: can macrophage polarization differentiate these two conditions microscopically?. (1st September 2020) - Harries, M.; Hardman, J.; Chaudhry, I.; Poblet, E.; Paus, R.
Summary: Background: Frontal fibrosing alopecia (FFA) is traditionally regarded as a variant of lichen planopilaris (LPP) based on histological features. Distinct clinical presentation, demographics and epidemiology suggest that differing pathogenic factors determine the final phenotype. Objectives: To map the hair follicle immune system in LPP and FFA by systematically comparing key inflammatory markers in defined hair follicle compartments. Methods: Lesional scalp biopsies from LPP and FFA and healthy controls were stained with the following immunohistochemical markers: CD1a and CD209, CD4, CD8, CD56, CD68, CD123, CXCR3, forkhead box (FOX)P3, mast cell tryptase and cKit. Macrophage polarization was explored using CD206, CD163, CD86, receptor for advanced glycation end products (RAGE), interleukin (IL)‐4 and IL‐13 on paired lesional and nonlesional LPP and FFA samples. Results: Increased numbers of CD8 +, CXCR3 + and FOXP3 + T cells and CD68 + macrophages were identified in the distal hair follicle epithelium and perifollicular mesenchyme in both LPP and FFA compared with controls. In both LPP and FFA, total and degranulated mast cells and CD123 + plasmacytoid dendritic cells were increased in the perifollicular mesenchyme adjacent to the bulge and infundibulum, whereas numbers of CD1a + and CD209 + dendritic cells were significantly reduced in the infundibulum connective tissue sheath. However, only with CD68 staining was a significant difference between LPP and FFA identified, with greater numbers of CD68 + cells in LPP samples. Furthermore, the identified macrophage polarization markers downregulated CD86 and upregulated CD163 and IL‐4 expression in lesional LPP compared with FFA samples. Conclusions: This comparative immunopathological analysis is the first to profile systematically the hair follicle immune system in LPP and FFA. Our analysis highlights a potential role of macrophages in disease pathobiology and suggests that macrophage polarization may differ between LPP and FFA, allowing microscopic differentiation. Linked Comment:  Kinoshita‐Ise. Br J Dermatol 2020; 183 :419–420 .